Answer:
see below
Step-by-step explanation:
The two marked points are equidistant from their average, which is ...
(-3 +9)/2 = 6/2 = 3
The distance they are from that average is 9-3 = 3 -(-3) = 6.
So, you want an expression that is equivalent to ...
|x -3| = 6
Subtracting 1 from both sides of this equation gives you the one seen in choice B:
|x -3| -1 = 5
Start from
and cross multiply the denominators (i.e. multiply both sides by
The result is
Expand the left hand side:
Bring all terms involving p to the left, and all terms involving q to the right:
Divide both sides by 21q:
Now we have a ratio between multiples of p and q. It's not exactly the one we want, though. Nevertheless, we can keep multiplying both sides by approriate constants in order to get the ratio we want:
Divide both sides by 5:
Multiply both sides by 3:
Answer:
see explanation
Step-by-step explanation:
Using the rules of exponents
• ⇔
• ⇔
(a)
= = 3
(b)
= = =
Answer:
Challenge #1:
Different examples:
2x+1=3x+2
4x+3=5x+4
3x+2=4x+3
Challenge #2:
Different examples:
2x+0=4x+1
3x+1=2x+5
6x+5=8x+6
Answer:
(-2x + 1 = 1x + 1) or (-4x + 2 = 2x + 2)
Step-by-step explanation: